A lipcsei ítélet - Szabó, István (Debreceni Jogi Műhely, 2005)
In Germany the new constitution published in 1919 established a brand new and democratically based state structure. Beside the traditional forum of administrative courts a new court system had been established in connection with public law jurisdiction. After Germany lost the first World War, general depression made a big impression on German state structure too. One of the most significant conflicts of this period had risen between the Empire and its biggest member state, Prussia. On 20th July 1932 president of the Empire suspended the Prussian autonomy and seized the power of directing the member state. The German Court of State had to verify this decision. Because of the fact that the court held its session in Lipche, this judgement is called as the famous judgement of Lipche. There are several really significant and dogmatically important factors in this decision, which help us understand the legal structure of that age in the German Empire. In this study I examine extraordinary power of the monarch in the Republic of Weimar and its special control by the courts. Constitution gave the right to the sovereign to obtain the regulations of the constitution by force in member states. There was a special right that entitled him using uncommon orders in case of attack against public order and public security. These rules ensured the unity of the Empire. The speciality of this judgement is that the Court qualified the order of the monarch unlawful because of the lack of the two circumstances mentioned above. To verify this decision court had to examine not only the nature of its procedure but the meaning of unity in the whole Empire, the aim of the constitution and these special rights of the monarch. The court focused on the examination of culpability in a member state. The conclusion is that intervention is legally based not only when a member state breaks the law with culpable behaviour but when breaking down of public order exists. In this special case the court split this practice and qualified the suspension of autonomy unlawful, but it found that other orders of the sovereign were acceptable. The result was that the autonomy was renovated but the Prussian government did not have the right in those cases, which were deprived by the monarch.